2019
DOI: 10.1016/j.forsciint.2019.109996
|View full text |Cite
|
Sign up to set email alerts
|

Volatilised pyrene: A phase 1 study demonstrating a new method of visualising fingermarks with comparisons to iodine fuming

Abstract: Pyrene is a fluorescent polycyclic aromatic hydrocarbon that can be volatilised under mild conditions. When fumed, pyrene is rapidly absorbed into the sebaceous residues of fingermarks, enabling their fluorescent visualisation upon excitation with ultraviolet radiation. This new means of fluorescent fingermark detection is more sensitive than the non-fluorescent iodine fuming approach for nonporous surfaces. This is demonstrated here in a phase 1 study using split-print comparisons on metal and glass surfaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…It is hoped that the chemical insights outlined in this work lead to new chemical strategies and reagents that generate improved contrast and are free of the presented drawbacks. While classed as a negative result, this work complements recent chemical studies in the field of fingermark visualisation, including an analogous negative result using 6-(N,N-dimethylamino)fulvene [14], the successful application of hydrolysed Nile blue A [15], functionalisation of both ninhydrin and 1,8-diazafluoren-9-one [16], the development of nanoparticle reagents [17,18], and the growing number of metal [19][20][21][22], and chemical [23,24], vapour-deposition methodologies.…”
Section: Introductionmentioning
confidence: 61%
“…It is hoped that the chemical insights outlined in this work lead to new chemical strategies and reagents that generate improved contrast and are free of the presented drawbacks. While classed as a negative result, this work complements recent chemical studies in the field of fingermark visualisation, including an analogous negative result using 6-(N,N-dimethylamino)fulvene [14], the successful application of hydrolysed Nile blue A [15], functionalisation of both ninhydrin and 1,8-diazafluoren-9-one [16], the development of nanoparticle reagents [17,18], and the growing number of metal [19][20][21][22], and chemical [23,24], vapour-deposition methodologies.…”
Section: Introductionmentioning
confidence: 61%
“…36 More recently, pyrene sublimation was assessed for copy paper and found to impart blue fluorescence, however this ultimately proved disadvantageous given optical brighteners in paper also emit blue, fluorescent background interference. 50 Pyrene showed a strong interaction with squalene, a major component of sebaceous residue, with limited interaction seen for alanine, a nonpolar amino acid. 50 This strongly suggested that pyrene primarily interacts with the nonpolar components of fingermark residue, namely sebaceous material, and it can be assumed that other polycyclic aromatic hydrocarbons behave in an analogous manner.…”
Section: Solvent-free Visualisation Treatmentsmentioning
confidence: 99%
“…36 More recently, pyrene sublimation was assessed for copy paper and found to impart blue fluorescence, however this ultimately proved disadvantageous given optical brighteners in paper also emit blue, fluorescent background interference. 50…”
Section: Solvent-free Visualisation Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary/Pilot studies – The following compounds were synthesized and successfully applied to sebum-rich fingermarks: dialkylated NB and NR derivatives [ 374 ], purine derivatives [ 375 ], and fumed pyrene [ 376 ]. The combination of iodine fuming with hexane or chloroform spraying was presented to detect fingermarks on various substrates [ 377 ].…”
Section: Fingermark Visualisationmentioning
confidence: 99%